Fuzzy Optimization of Construction Engineering Project Schedule Based on Critical Chain Management - Jianbing LIU; Hong REN; Junshu DU (Institute of Advanced Engineering and Science, 2013)
Critical chain management was the very important theory innovation in the development of construction project schedule management field in recent years. Compared with the traditional methods of construction project schedule management, the methods of critical chain management considered resource constraints into construction project schedule management, the construction project cycle was shortened and the efficiency was enhanced by using the dynamic thinking and circulation pattern to manage whole project. In view of the progress of critical chain management of the article, fuzzy theory was used to calculate and optimize the buffer zone sizes with the determination of the buffer size of the existing resources in certain critical chain management so as to shorten the cycle. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3591